2008
DOI: 10.1074/jbc.m802312200
|View full text |Cite
|
Sign up to set email alerts
|

Laminin-332 Is a Substrate for Hepsin, a Protease Associated with Prostate Cancer Progression

Abstract: Hepsin, a cell surface protease, is widely reported to be overexpressed in more than 90% of human prostate tumors. Hepsin expression correlates with tumor progression, making it a significant marker and target for prostate cancer. Recently, it was reported that in a prostate cancer mouse model, hepsin up-regulation in tumor tissue promotes progression and metastasis. The underlying mechanisms, however, remain largely uncharacterized. Hepsin transgenic mice displayed reduced laminin-332 (Ln-332) expression in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 59 publications
(50 reference statements)
7
67
1
Order By: Relevance
“…Hao et al reported that LAMB3 and LAMC2 mRNA could be detected in prostate cancer tissue, suggesting that the mechanism is post-transcriptional (23). Cleavage of ␤3 and ␥2 proteins by matrix metalloproteases and hepsin has also been described (7,24,25). These results may appear at odds with those reported here; however, more than one mechanism may account for the reduction of laminin-332 immunoreactivity in prostate cancer.…”
Section: Discussioncontrasting
confidence: 57%
“…Hao et al reported that LAMB3 and LAMC2 mRNA could be detected in prostate cancer tissue, suggesting that the mechanism is post-transcriptional (23). Cleavage of ␤3 and ␥2 proteins by matrix metalloproteases and hepsin has also been described (7,24,25). These results may appear at odds with those reported here; however, more than one mechanism may account for the reduction of laminin-332 immunoreactivity in prostate cancer.…”
Section: Discussioncontrasting
confidence: 57%
“…Hepsin activates pro-HGF by cleavage at KQLR#V (19,34). The scissile peptide sequence of pro-MSP, SKLR#V, has strong similarity to that of pro-HGF as well as to the SQLR#L cleavage sequence of the recently identified hepsin substrate laminin-332 (36), suggesting that pro-MSP could potentially be a hepsin substrate. Here, we provide several lines of evidence to show that hepsin is an efficient pro-MSP activator that generates the biologically active 2-chain a/b-heterodimeric MSP signaling molecule.…”
Section: Gene Expression Profiles Of Msp and Hepsin In Comparison To mentioning
confidence: 99%
“…Moreover, gene expression analyses have also implicated hepsin in ovarian cancer (30), renal cell carcinoma (31,32), and endometrial cancer (33). A putative function of hepsin in tumor progression could be related to its enzymatic activity toward the macromolecular substrates pro-HGF (19,34), pro-uPA (35), and laminin-332 (36). Additional substrates that have been identified are coagulation factors (37) and pro-prostasin (38).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of hepsin in basal prostate epithelial cells of mice leads to the disorganization of the basement membrane (47). Substrates linked to carcinogenesis that can be cleaved by hepsin ex vivo are coagulation factor VII, pro-hepatocyte growth factor, laminin 332, and pro-urokinase plasminogen activator (46,49).…”
Section: Physiology and Pathobiology Of Ttspsmentioning
confidence: 99%